The Effect of Dynamic Capability and Market Orientation on MSME Marketing Performance in Malang City - Cahyaningati, Nilam; Handayanto, Eko; Sa’diyah, Chalimatuz (Universitas Muhammadiyah Malang, 2023)
The purpose of this study was to find out how dynamic capabilities and market orientation influence the marketing performance of MSMEs in Malang City. This research uses quantitative techniques. All MSMEs in Malang City are included in the population used. Sampling using a probability sample with stratified random sampling. There were 382 respondents as samples and questionnaires were used to collect data. Data analysis technique with multiple linear regression. This study found that dynamic capabilities and market orientation have a relationship that has a significant positive effect on the marketing performance of MSMEs. The need to concentrate on dynamic capabilities and market orientation because these two things play an important role in improving the marketing performance of MSMEs in Malang City.